PENGARUH PARTISIPASI MASYARAKAT DALAM GERAKAN 3M (MENGURAS, MENUTUP DAN MENGUBUR) TERHADAP PENANGGULANGAN DEMAM BERDARAH DENGUE DI KELURAHAN TANJUNG PENYEMBAL KOTA DUMAI TAHUN 2020 - Farida Marbun (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2022)
This study aims to analyze the Effect of Community Participation (Willingness, Capability and Opportunities) in the 3M Reservoir Movement for Management of Dengue Hemorrhagic Fever (DHF) in Tanjung Penyembal Village, Sungai Sembilan District, Dumai City in 2020. The study used was a cross-sectional study using an explanatory research approach to analyze the effect of community participation (willingness, ability and opportunity) on the prevention of Dengeu Hemorrhagic Fever (DHF) in Tanjung Penyembal Kelurahan with 80 respondents. The analysis showed that the willingness variable (p = 0.001), ability (p = 0.007) and chance (p = 0.005) influenced the prevention of DHF. It is recommended to the Department of Health to be able to involve the community since the beginning of the implementation of the DHF prevention program, and to form a special team in the community to provide information and regular counseling to other communities, in order to increase the willingness, knowledge and ability of the community on how to handle DHF. It is expected that the Department of Health should establish a Training Program for Community Independence in the Prevention of Dengue Fever, wherein later this Village can be used as a Pilot Village for Community Involvement in Respecting Dengue in the region and also improve supervision and sweep larvae, as well as provide sanctions to the community where DHF mosquito larvae are present. The village / kelurahan apparatus should be able to work together with other communities to carry out environmental cleanliness (DHF PSN) to control dengue mosquito larvae.